2005
DOI: 10.1258/0023677052886510
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic variables in healthy guineapigs anaesthetized with ketamine–xylazine

Abstract: SummaryEchocardiographic parameters were recorded, measured and statistically analysed on a population of 12 male Hartley albino guineapigs under ketamine-xylazine anaesthesia. Additionally, the effect of body weight on these parameters and the correlation between the parameters were assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…11 Lateral recumbency is the preferred positioning, although a standing position may be used for small breeds (Figure 2). Similarly, normal echocardiographic values have been reported for the chinchilla 12 ( Chinchilla laniger ), guinea pig 13 ( Cavia porcellus ), Syrian hamster 14 ( Mesocriecetus auratus ) and ferret ( Mustela putorius furo ) 1517 . While the heart is located approximately between the third and fifth intercostal spaces in most small pet mammals, its location is more caudal (between sixth and eighth ribs) in ferrets and therefore a more caudal placement of the transducer is required for echocardiography in these patients.…”
Section: Echocardiography In Mammalssupporting
confidence: 54%
“…11 Lateral recumbency is the preferred positioning, although a standing position may be used for small breeds (Figure 2). Similarly, normal echocardiographic values have been reported for the chinchilla 12 ( Chinchilla laniger ), guinea pig 13 ( Cavia porcellus ), Syrian hamster 14 ( Mesocriecetus auratus ) and ferret ( Mustela putorius furo ) 1517 . While the heart is located approximately between the third and fifth intercostal spaces in most small pet mammals, its location is more caudal (between sixth and eighth ribs) in ferrets and therefore a more caudal placement of the transducer is required for echocardiography in these patients.…”
Section: Echocardiography In Mammalssupporting
confidence: 54%
“…The mean value found for left ventricular ejection fraction (EF) values was similar to standard values for minipigs [27] and lower when compared to New Zealand rabbits [41], guinea pigs and non-anesthetized agoutis [10]. This difference can be justified by the depressant effects of ketamine, which promotes early ventricular depolarization, interfering with blood pressure, heart rate and cardiac output [28,30].…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have demonstrated normal echocardiographic parameters for domestic animals such as dogs, cats, horses, sheep [7,9,27], as well as wild rodents such as prairie dogs (Cynomys ludovicianus) [20], guinea pigs (Cavia porcellus) [10] and New Zealand rabbits [41]. However, although presumptive normal echocardiographic values were reported for non-anesthetized agoutis [15], this is the first study to show the measurement of these variables for chemically contained agoutis, in addition to the use of strain and strain rate by speckle tracking in the evaluation of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information on normal ranges in guinea pigs. Data published until now are based in values obtained under sedation with ketamine and xylazine (Çetin and others 2005). Conversely, ketamine has been proven to cause negative inotropic effects and cardiovascular depression in guinea pigs (Endou and others 1992, Ramsey 2008).…”
Section: Outcome and Follow-upmentioning
confidence: 99%